Caracterização mineralógica de azulejos de Salvador e Belém dos séculos XVI, XVII e XIX - SANJAD, Thais Alessandra Bastos Caminha (2014)
The present article is a study about the mineralogical composition of ancient tiles from centuries XVI, XVII and XIX, found in Belém and Salvador, in order to interpret the possible raw material and burning temperature. Quartz was identified in all samples. Other crystalline phases found are mullite, cristobalite, calcite, anorthite, hematite, gehlenite, diopside and wollastonite. Based on the probable raw material and probable burning temperature it was possible to organize the samples into three groups: group 1 - kaolinite and quartz, T between 1200º and 1728º C; group 2 - kaolinite, calcite and/or dolomite and iron oxide or hydroxide, T between 900º e 1200ºC; group 3 - quartz, clay minerals (probably kaolinite), calcite and/or dolomite, iron oxide or hydroxide, and T between 1200º e 1565º C.